The use of compost in afforestation of Mediterranean areas: Effects on soil properties and young tree seedlings. - Larchevêque, Marie; Ballini, Christine; Korboulewsky, Nathalie; Montès, Nicolas (The Science of the total environment, 2006)
In Mediterranean frequently burnt areas, fire and erosion result in the decrease of soil fertility, so afforestation is a major concern. We carried out an in situ experiment of compost amendment to improve survival and growth of planted tree seedlings. One-year-tree seedlings of native species (Quercus ilex, Pinus halepensis and Pinus pinea) were planted on a frequently burnt calcareous site. Three rates of fresh co-composted sewage sludge and greenwastes (control without compost, 20 and 40 kg m(-2) of compost) were incorporated into the soil at each seedling stem. Changes of soil properties and tree development were studied during 3 years (2001-2003) and 2 years (2002-2003) respectively. The compost improved survival of Quercus ilex and Pinus pinea seedlings in severe drought conditions, but had no effect on Pinus halepensis. For all species seedling length and radial growth and NPK nutrition were increased for both rates of amendment. Amendment improved soil fertility, but available P concentration increased 13 fold in the neighbouring soil of seedlings amended at the maximal rate compared to control. However, amendment did not significantly increase concentrations of Cd, Cr, Ni and Pb in soils or tree seedlings. It increased Cu and Zn total and available concentrations in soils, while foliar Cu and Zn concentrations in the seedlings remained similar in all plots. Compost can efficiently help afforestation of dry soils with low organic matter content. However, sewage sludge concentrations in P, and to a lesser extent in Cu and Zn, limit rates of application that can be applied without environmental hazard.
Keywords: Afforestation; Pinus halepensis; Pinus pinea; Quercus ilex; Sewage sludge compost; Trace metals

The use of compost in afforestation of Mediterranean areas: Effects on soil properties and young tree seedlings. - Larchevêque, Marie; Ballini, Christine; Korboulewsky, Nathalie; Montès, Nicolas (The Science of the total environment, 2006)
In Mediterranean frequently burnt areas, fire and erosion result in the decrease of soil fertility, so afforestation is a major concern. We carried out an in situ experiment of compost amendment to improve survival and growth of planted tree seedlings. One-year-tree seedlings of native species (Quercus ilex, Pinus halepensis and Pinus pinea) were planted on a frequently burnt calcareous site. Three rates of fresh co-composted sewage sludge and greenwastes (control without compost, 20 and 40 kg m(-2) of compost) were incorporated into the soil at each seedling stem. Changes of soil properties and tree development were studied during 3 years (2001-2003) and 2 years (2002-2003) respectively. The compost improved survival of Quercus ilex and Pinus pinea seedlings in severe drought conditions, but had no effect on Pinus halepensis. For all species seedling length and radial growth and NPK nutrition were increased for both rates of amendment. Amendment improved soil fertility, but available P concentration increased 13 fold in the neighbouring soil of seedlings amended at the maximal rate compared to control. However, amendment did not significantly increase concentrations of Cd, Cr, Ni and Pb in soils or tree seedlings. It increased Cu and Zn total and available concentrations in soils, while foliar Cu and Zn concentrations in the seedlings remained similar in all plots. Compost can efficiently help afforestation of dry soils with low organic matter content. However, sewage sludge concentrations in P, and to a lesser extent in Cu and Zn, limit rates of application that can be applied without environmental hazard.
The following values have no corresponding Zotero field: accession-num: 16762400
Keywords: Afforestation; Pinus halepensis; Pinus pinea; Quercus ilex; Sewage sludge compost; Trace metals

Trace metal fluxes in bulk deposition, throughfall and stemflow at two evergreen oak stands in NE Spain subject to different exposure to the industrial environment - Avila, Anna; Rodrigo, Anselm (Atmospheric Environment, 2004)
We compare here the bulkdeposition, throughfall and stemﬂow ﬂuxes of dissolved trace metals in two holm oak (Quercus ilex L.) forests in the Montseny Mountains (NE Spain) with the aim of: (1) applying different methods to distinguish between dry deposition and canopy leaching and (2) to add to the almost non-existing deposition measurements for dissolved Cu, Pb, Mn, V, Zn, Ni and Cd in two Spanish forests differentially exposed to the urban and industrial environment. No signiﬁcant differences in mean bulkdeposition concentrations or ﬂuxes were found between sites, indicating little differential effect of the urban/industrial environment on bulkprecipitation chemistry. At both sites, throughfall and stemﬂow ﬂuxes increased relative to bulkdeposition for all elements, except for Zn and Cd. The relative contribution of leaching and dry deposition was evaluated through: (1) the seasonal variability of throughfall, (2) regressions of element ﬂuxes on water ﬂux in net throughfall, (3) washing branches and metacrylate plates, and (4) the sequential washing of branches. Results indicated that leaching was the main enrichment process for Mn. For Ni, except the sequential washings, all other evidences also pointed to leaching. For Cu, Pb, Zn, Cd and V there was ample evidence for dry deposition. The fact that Zn and Cd had negative net throughfall ﬂuxes indicated that canopy uptake was greater than deposition (wet plus dry). Net throughfall ﬂuxes pointed to higher dry deposition onto the canopies in the more exposed site, but the occurrence of uptake impeached quantiﬁcation. Therefore, dry deposition was estimated from the recovered quantities from experimental washings of foliage, taken to represent the impaction of small particles onto the canopy. The foliage-wash ﬂuxes were, for Zn, Cu and Pb, respectively, 407, 25 and 16 g ha 1 yr 1 at the sheltered site and 423, 38 and 26 g ha 1 yr 1 at the exposed site. Deposition in bulkprecipitation (wet deposition+an unknown fraction of dry deposition mostly accounted by coarse particles settling gravitationally) was lower: 222, 6.3 and 6.5 g ha 1 yr 1 for Zn, Cu and Pb, respectively, averaged for the two sites
Keywords: Dry deposition; Leaching; Mediterranean forests; surrogate surfaces; throughfall; Trace metals

Trace metal fluxes in bulk deposition, throughfall and stemflow at two evergreen oak stands in NE Spain subject to different exposure to the industrial environment - Avila, Anna; Rodrigo, Anselm (Atmospheric Environment, 2004)
We compare here the bulkdeposition, throughfall and stemﬂow ﬂuxes of dissolved trace metals in two holm oak (Quercus ilex L.) forests in the Montseny Mountains (NE Spain) with the aim of: (1) applying different methods to distinguish between dry deposition and canopy leaching and (2) to add to the almost non-existing deposition measurements for dissolved Cu, Pb, Mn, V, Zn, Ni and Cd in two Spanish forests differentially exposed to the urban and industrial environment. No signiﬁcant differences in mean bulkdeposition concentrations or ﬂuxes were found between sites, indicating little differential effect of the urban/industrial environment on bulkprecipitation chemistry. At both sites, throughfall and stemﬂow ﬂuxes increased relative to bulkdeposition for all elements, except for Zn and Cd. The relative contribution of leaching and dry deposition was evaluated through: (1) the seasonal variability of throughfall, (2) regressions of element ﬂuxes on water ﬂux in net throughfall, (3) washing branches and metacrylate plates, and (4) the sequential washing of branches. Results indicated that leaching was the main enrichment process for Mn. For Ni, except the sequential washings, all other evidences also pointed to leaching. For Cu, Pb, Zn, Cd and V there was ample evidence for dry deposition. The fact that Zn and Cd had negative net throughfall ﬂuxes indicated that canopy uptake was greater than deposition (wet plus dry). Net throughfall ﬂuxes pointed to higher dry deposition onto the canopies in the more exposed site, but the occurrence of uptake impeached quantiﬁcation. Therefore, dry deposition was estimated from the recovered quantities from experimental washings of foliage, taken to represent the impaction of small particles onto the canopy. The foliage-wash ﬂuxes were, for Zn, Cu and Pb, respectively, 407, 25 and 16 g ha 1 yr 1 at the sheltered site and 423, 38 and 26 g ha 1 yr 1 at the exposed site. Deposition in bulkprecipitation (wet deposition+an unknown fraction of dry deposition mostly accounted by coarse particles settling gravitationally) was lower: 222, 6.3 and 6.5 g ha 1 yr 1 for Zn, Cu and Pb, respectively, averaged for the two sites
Keywords: Dry deposition; Leaching; Mediterranean forests; surrogate surfaces; throughfall; Trace metals

Leaf Contamination by Atmospheric Pollutants as Assessed by Elemental Analysis of Leaf Tissue, Leaf Surface Deposit and Soil - Alfani, Anna; Maisto, Giulia; Iovieno, Paola; Rutigliano, Flora a.; Bartoli, Giovanni (Journal of Plant Physiology, 1996)
In order to evaluate the influence of air pollutants influx on leaf elemental composition, the concentration ofN, S, Cu, Fe and Pb were analyzed in the surface deposit and tissue of Quercus ilex L. leaves from 8 sites of the urban area of Naples. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total contents of Nand S and for available contents ofCu, Fe and Pb. In the leafsurface deposit S content was high though significantly (P<O.OOl) lower than in the leaf tissue, whilst N was not detectable. Cu, Pb and Fe contents in leafsurface deposit were conspicuous. The Pb content was higher in the leafsurface deposit than in the leaf tissue. No correlation between leaftissue and surface deposit contents was found for S or for Fe. By contrast, positive and significant correlations (P < 0.01) were found between leaf deposit and leaf tissue for both Cu and Pb. Nand S contents in the leaves were not correlated to the respective contents in the soil and the same was also found for Cu and Fe. In contrast with the presence of limiting concentrations in the soil, N, S and Fe leaf contents were significantly higher than in the leaves from remote sites. The data suggest that direct uptake of airborne pollutants, in addition to root absorption, may influence leaf elemental composition of Q. ilex L. leaves.
Keywords: air pollution; leaf contamination; nitrogen; Quercus ilex L; sulphur; Trace metals

Leaf Contamination by Atmospheric Pollutants as Assessed by Elemental Analysis of Leaf Tissue, Leaf Surface Deposit and Soil - Alfani, Anna; Maisto, Giulia; Iovieno, Paola; Rutigliano, Flora a; Bartoli, Giovanni (Journal of Plant Physiology, 1996)
In order to evaluate the influence of air pollutants influx on leaf elemental composition, the concentration ofN, S, Cu, Fe and Pb were analyzed in the surface deposit and tissue of Quercus ilex L. leaves from 8 sites of the urban area of Naples. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total contents of Nand S and for available contents ofCu, Fe and Pb. In the leafsurface deposit S content was high though significantly (P<O.OOl) lower than in the leaf tissue, whilst N was not detectable. Cu, Pb and Fe contents in leafsurface deposit were conspicuous. The Pb content was higher in the leafsurface deposit than in the leaf tissue. No correlation between leaftissue and surface deposit contents was found for S or for Fe. By contrast, positive and significant correlations (P < 0.01) were found between leaf deposit and leaf tissue for both Cu and Pb. Nand S contents in the leaves were not correlated to the respective contents in the soil and the same was also found for Cu and Fe. In contrast with the presence of limiting concentrations in the soil, N, S and Fe leaf contents were significantly higher than in the leaves from remote sites. The data suggest that direct uptake of airborne pollutants, in addition to root absorption, may influence leaf elemental composition of Q. ilex L. leaves.
The following values have no corresponding Zotero field: publisher: Gustav Fischer Verlag, Stuttgart
Keywords: air pollution; leaf contamination; nitrogen; Quercus ilex L; sulphur; Trace metals